Structural mosaicity and electrical properties of pyrolitic SnO2:F thin films - Garces Pineda, Felipe Andres (2013)
In this work we present structural and electrical properties of SnO2:F thin films deposited on glass substrate by the spray pyrolysis technique. The precursors of SnO2:F were synthesized by a sol?gel method, starting from a SnCl4·5H2O/ethanol mixture and using NH4F/H2O as a dopant. Different properties were observed depending on the deposition time of the films. The structural characteristics of the layers, like crystal size, preferential growth orientation and mosaicity, were studied by X-ray diffraction. These results were compared and correlated with those obtained from electrical measurements, such as carrier density, Hall mobility and resistivity. We have found that for longer deposition times, the mosaicity of the crystallites increases. This process is accompanied by a decrease in the resistivity.